2018
DOI: 10.3389/fimmu.2018.01183
|View full text |Cite
|
Sign up to set email alerts
|

Sialylated Autoantigen-Reactive IgG Antibodies Attenuate Disease Development in Autoimmune Mouse Models of Lupus Nephritis and Rheumatoid Arthritis

Abstract: Pro- and anti-inflammatory effector functions of IgG antibodies (Abs) depend on their subclass and Fc glycosylation pattern. Accumulation of non-galactosylated (agalactosylated; G0) IgG Abs in the serum of rheumatoid arthritis and systemic lupus erythematosus (SLE) patients reflects severity of the diseases. In contrast, sialylated IgG Abs are responsible for anti-inflammatory effects of the intravenous immunoglobulin (pooled human serum IgG from healthy donors), administered in high doses (2 g/kg) to treat au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 79 publications
(127 reference statements)
2
44
0
Order By: Relevance
“…All these variables can influence the functionality of immune organs, cells and molecules. Glycans are practically present in all components of the immune system . However, their distribution is not random.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these variables can influence the functionality of immune organs, cells and molecules. Glycans are practically present in all components of the immune system . However, their distribution is not random.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the pivotal and widespread role of glycosylation is made evident by the array of molecules of the immune system that are glycosylated. These include immunoglobulins, adhesion molecules (eg, integrins and selectins), PRRs (eg, toll like receptors—TLRs—and lectins) and complement molecules, cytokines, chemokines and (many of) their receptors …”
Section: Introductionmentioning
confidence: 99%
“…Immunoglobulins (Igs) are glycosylated molecules, and by now, it is clear that the N-glycans of the Fc-fragment strongly influence IgG-Fcγ receptor interactions and thus the Fcmediated effector mechanisms [101,102]. Several studies have demonstrated that NAbs usually exhibit a sialylated pattern which confers an anti-inflammatory nature, in contrast to Ag-specific adaptive Abs that are either agalactosylated or asialylated and exhibit proinflammatory properties [103][104][105]. Compared to healthy individuals, there is a marked change of serum Ig glycosylation in individuals with autoimmune diseases, infections, and tumors [106][107][108][109][110][111][112][113].…”
Section: Antibody Glycosylation Profiling In Health and Cancermentioning
confidence: 99%
“…Some elegant studies have shown the potential impact of glycan regulation in multiple aspects of RA pathophysiology, for example reduced sialylation of N-glycans is a feature of pathogenic immunoglobulins in RA patients and their glycosylation profile shows predictive potential for disease progression [13][14][15][16][17] . Besides, galectins, a family of proteins that bind to galactose-containing glycans, are key modulators of synovial inflammation [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%